Harley Hahn's Internet & Web Golden Directory - Hahn, Harley (Berkeley Osborne/McGraw-Hill, 2000)
With over 160 categories offering thousands of references, this directory has been significantly upgraded to reflect the full range of Web services for 2000. Sections include web portals, a look back at the last 100 years and expanded coverage of shopping and genealogy; the CD-ROM is hot-linked.
Include Index.
Keywords: Internet addresses -- Web sites -- Computer network resources -- World Wide Web